Multiresponse Optimization of Inoculum Conditions for the Production of Amylases and Proteases by Aspergillus awamori in Solid-State Fermentation of Babassu Cake - de Castro, Aline Machado (SAGE-Hindawi Access to Research, 2011)
This work aimed at investigating the simultaneous production of amylases and proteases by solid-state fermentation (SSF) of babassu cake using Aspergillus awamori IOC-3914. By means of experimental design techniques and the desirability function, optimum inoculum conditions (C/N ratio of propagation medium, inoculum age, and concentration of inoculum added to SSF medium) for the production of both groups of enzymes were found to be 25.8, 28.4 h, and 9.1 mg g(−1), respectively. Significant influence of both initial C/N ratio and inoculum concentration was observed. Optimum amylolytic activities predicted by this multiresponse analysis were validated by independent experiments, thus indicating the efficacy of this approach.